Analysis of used clothing business competition with predatory pricing in the local clothing industry - Maria Eleonora Novena Pritasari (Faculty of Law, University of Merdeka Malang, 2022)
This research intends to examine juridically about used clothes that are offered with relatively cheap quality. This business is developing in Indonesia and can even kill the local clothing industry because the price difference is very large. This clothing business can weaken the local industry in the small and medium market, especially when local entrepreneurs want to improve the quality of their products so that they cannot compete with foreign products. Sales of used clothing due to low prices indicate competitive prices. The strategy of selling products at higher prices worries the Indonesian government because it can lead to unfair business practices. The approach is normative jurisprudence, namely the study of legal basis and standards. The results of this study indicate that the sale of used clothing is not part of predatory pricing practices. However, selling used clothing at relatively low prices reduces consumer interest in local products and can hurt the economy of the local clothing industry.How to cite item:Â Pritasari, M. (2022). Analysis of used clothing business competition with predatory pricing in the local clothing industry.Â Jurnal Cakrawala Hukum, 13(3), 291-299. DOI:https://doi.org/10.26905/idjch.v13i3.8912.